J.K. Lasser's your income tax 2022 : for preparing your 2021 tax return - J.K. Lasser Institute (Hoboken, New Jersey : Wiley, 2022)
"J.K. Lasser's Your Income Tax 2022: For Preparing Your 2021 Tax Return delivers hands-on and practical advice for everyday taxpayers getting ready to file their 2021 taxes. On top of info about the latest changes to the 2021 tax code, you'll get worksheets and forms you can use to file your taxes. You'll also find the most current advice on how to maximize your deductions and credits and keep as much money in your pocket-and out of Uncle Sam's-as possible"--
Includes index.
109497
Keywords: Income tax -- United States -- Handbooks, manuals, etc; Tax returns -- United States -- Handbooks, manuals, etc; Handbooks and manuals